PERUBAHAN PELAMINAN MINANGKABAU (STUDI KASUS PADA PELAMINAN USAHA IBU) - Marlina, Apri; Efi, Agusti; Yusmerita, Yusmerita (Journal of Home Economics and Tourism, 2013)
Alongwithsocial and cultural changes, the altarhasundergone manychanges, whichhave beenused asweddingservice industryshifted,fromaisletoaislemoderntraditionssuch astheCapitalDistrictBusinessLubukBegalungPadang. The method usedin this study wasdescriptivequalitativemethod. Typesof datain the form ofprimary and secondary data.Techniques ofdata collectionthrough observations, interviewsanddocumentation.Datawere analyzedwithan interactivemodel analysistechniquesand conclusion. The resultsarein theform ofweddingtraditionsEnterprisesmotherbasicallyrectangularconsisting ofrooms, while theform ofthe modernaltar-shaped throne. Colorandtype ofmaterial used on thealtarin thetradition ofMotherof Businessis red, blackandyellow, while themodernweddingcolormixonlytwocolors, such asbright colorscombinedwithsilverandgoldcolors. As well asornamentsusedonmodernweddingis much differentinCapitalBusinessbutmakingit easier. Â  Kata kunci: pelaminan, Minangkabau, Usaha Ibu